2015
DOI: 10.1124/dmd.114.062745
|View full text |Cite
|
Sign up to set email alerts
|

Brain Exposure of Two Selective Dual CDK4 and CDK6 Inhibitors and the Antitumor Activity of CDK4 and CDK6 Inhibition in Combination with Temozolomide in an Intracranial Glioblastoma Xenograft

Abstract: Effective treatments for primary brain tumors and brain metastases represent a major unmet medical need. Targeting the CDK4/CDK6-cyclin D1-Rb-p16/ink4a pathway using a potent CDK4 and CDK6 kinase inhibitor has potential for treating primary central nervous system tumors such as glioblastoma and some peripheral tumors with high incidence of brain metastases. We compared central nervous system exposures of two orally bioavailable CDK4 and CDK6 inhibitors: abemaciclib, which is currently in advanced clinical deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
177
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 220 publications
(189 citation statements)
references
References 63 publications
11
177
0
1
Order By: Relevance
“…The largest increase in brain exposure was observed in the Mdr1a/b 2/2 Bcrp1 2/2 mice, with an ∼115-fold increase in brain distribution, again showing that both transporters are critical in limiting delivery. Consistent with recent reports (de Gooijer et al, 2015;Raub et al, 2015), we have shown that the efflux transporters P-gp and BCRP play a significant role in the brain delivery of palbociclib. Furthermore, our data in the current study indicate that the limited brain delivery of palbociclib may be the reason behind the lack of efficacy of palbociclib in the orthotopic GBM22 model.…”
Section: Discussionsupporting
confidence: 78%
“…The largest increase in brain exposure was observed in the Mdr1a/b 2/2 Bcrp1 2/2 mice, with an ∼115-fold increase in brain distribution, again showing that both transporters are critical in limiting delivery. Consistent with recent reports (de Gooijer et al, 2015;Raub et al, 2015), we have shown that the efflux transporters P-gp and BCRP play a significant role in the brain delivery of palbociclib. Furthermore, our data in the current study indicate that the limited brain delivery of palbociclib may be the reason behind the lack of efficacy of palbociclib in the orthotopic GBM22 model.…”
Section: Discussionsupporting
confidence: 78%
“…Finally, because preclinical data have shown that abemaciclib crosses the blood-brain barrier and prolongs survival in intracranial human brain tumor xenografts [24], paired cerebrospinal fluid (CSF) and unbound plasma concentrations of abemaciclib were obtained from 10 patients with glioblastoma in the JPBA trial [21]. The results showed that abemaciclib concentrations detected in the CSF approximate those in plasma.…”
Section: Abemaciclibmentioning
confidence: 99%
“…Tumor growth inhibition is observed in multiple other human cancer xenograft models, including those derived from non-small cell lung cancer (NSCLC), melanoma, glioblastoma, and mantle cell lymphoma (21)(22)(23). Abemaciclib distributes across the blood-brain barrier and prolongs survival in an intracranial glioblastoma xenograft model ( 24 ), suggesting potential effi cacy against primary and metastatic tumors involving the central nervous system.…”
Section: Introductionmentioning
confidence: 99%